Building and Applying Al-Insyirah Theology: Muhammadiyah's Philanthropic Response to the COVID-19 Crisis - Muhammad Alfreda Daib Insan Labib; Khulanah Khulanah; Muhammad Ghossan Nazhif Dhiya’elhaq; Hanan Aslamiyah Thoriq (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2024)
This article explores the theological concept of al-Insyirah within Muhammadiyah, a concept introduced by Haedar Nashir. Al-Insyirah theology is relatively new compared to the more established theologies of al-Ma'un and al-'Ashr, making it a rare subject of study. This gap in research motivated the study of al-Insyirah theology. The research employs a descriptive-analytical method, presenting and then analyzing collected data. The article covers three main areas: the background of al-Insyirah theology, its theological construction, and its manifestation within the Muhammadiyah community. The study concludes that al-Insyirah theology emerged as a response to the challenges posed by the COVID-19 pandemic. It aims to inspire optimism and resilience in the face of difficulties. Manifestations of this theology include the growth of Muhammadiyah's charitable ventures (Amal Usaha Muhammadiyah) and social movements, which contribute to shaping a progressive future for Islam, particularly among Indonesian Muslims.